2021
DOI: 10.1186/s12877-021-02650-8
|View full text |Cite
|
Sign up to set email alerts
|

Dementia care and the role of guideline adherence in primary care: cross-sectional findings from the DemTab study

Abstract: Background General practitioners (GPs) play a key role in the care of people with dementia (PwD). However, the role of the German Dementia Guideline in primary care remains unclear. The main objective of the present study was to examine the role of guideline-based dementia care in general practices. Methods A cross-sectional analysis of data obtained from the DemTab study was conducted. Descriptive analyses of sociodemographic and clinical characte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 65 publications
1
12
1
Order By: Relevance
“…First, due to the cross-sectional design we cannot draw conclusions about causal relationships. Second, although the response rate of the present study is comparable to previous primary care research [ 23 , 46 ], the overall response rate was rather low. This leads to limitations in the generalizability of the sample.…”
Section: Discussionsupporting
confidence: 69%
“…First, due to the cross-sectional design we cannot draw conclusions about causal relationships. Second, although the response rate of the present study is comparable to previous primary care research [ 23 , 46 ], the overall response rate was rather low. This leads to limitations in the generalizability of the sample.…”
Section: Discussionsupporting
confidence: 69%
“…However, comparing present sociodemographic characteristics of participating PCPs with previous, representative PCPs samples, demographic characteristics such as age are comparable to some extent (Deselaers, 2021). Further, in comparison to a Berlin and sounding areas based PCP sample, age and sex of the present study are very similar, while years of experience as a PCP are higher among PCPS of the present study (Lech et al, 2021). Further, the present study only focused on two geographical areas (Berlin and the surroundings) and only represents the perspectives of PCPs.…”
Section: Limitationsmentioning
confidence: 44%
“…A detailed overview of the recruitment strategies and rates can be obtained elsewhere. 12 To sum up, PCP were recruited through three recruitment rounds which included the dissemination of advertisements and calls for participation in primary care related networks, cold calls of randomly drawn PCP from a database of the Statutory Health Insurance Physicians in Berlin, and face-to-face recruitment of PCP in their general practices in Berlin. Inclusion criteria for PCP were as follows: (1) operating as PCP, (2) meeting technical requirements (Internet connection), (3) willing to participate in a training, and (4) signed cooperation agreement.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…However, some measures were undertaken and published to ensure the validation of the assessment. 12 For example, originally, the checklists were composed in a dichotomous format (yes/no), but included the category "not applicable". Baseline data analysis of the DemTab Study revealed inconsistencies in the selection of the category "not applicable" resulting in uncertainty how and when this category was chosen by participants.…”
Section: Primary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation